Development of an RNase H2 activity assay for clinical screening - Schulz, Marian Simon; Sartorius von Bach, Cay Bennet; Marinkovic, Emilija; Günther, Claudia; Behrendt, Rayk; Roers, Axel (Journal of Clinical Medicine, 2023)
As the key enzyme mediating ribonucleotide excision repair, RNase H2 is essential for the removal of single ribonucleotides from DNA in order to prevent genome damage. Loss of RNase H2 activity directly contributes to the pathogenesis of autoinflammatory and autoimmune diseases and might further play a role in ageing and neurodegeneration. Moreover, RNase H2 activity is a potential diagnostic and prognostic marker in several types of cancer. Until today, no method for quantification of RNase H2 activity has been validated for the clinical setting. Herein, validation and benchmarks of a FRET-based whole-cell lysate RNase H2 activity assay are presented, including standard conditions and procedures to calculate standardized RNase H2 activity. Spanning a wide working range, the assay is applicable to various human cell or tissue samples with overall methodological assay variability from 8.6% to 16%. Using our assay, we found RNase H2 activity was reduced in lymphocytes of two patients with systemic lupus erythematosus and one with systemic sclerosis carrying heterozygous mutations in one of the RNASEH2 genes. Implementation of larger control groups will help to assess the diagnostic and prognostic value of clinical screening for RNase H2 activity in the future.